Respiratory viruses in rural Zambia before and during the COVID‐19 pandemic. Issue 7 (8th June 2022) - Loevinsohn, Gideon; Hamahuwa, Mutinta; Hardick, Justin; Sinywimaanzi, Pamela; Fenstermacher, Katherine Z. J.; Munachoonga, Passwell; Weynand, Austin; Monze, Mwaka; Manabe, Yukari C.; Gaydos, Charlotte A.; Rothman, Richard E.; Pekosz, Andrew; et al.
Abstract: Objectives: With the emergence of the COVID‐19 pandemic, restrictions were implemented globally to control the virus. Data on respiratory pathogens in sub‐Saharan Africa during the COVID‐19 pandemic are scarce. This analysis was conducted to evaluate patterns of respiratory pathogens in rural Zambia before and during the first year of the pandemic. Methods: Surveillance was established in December 2018 at Macha Hospital in southern Zambia. Patients with respiratory symptoms in the outpatient and inpatient clinics were recruited. Nasopharyngeal samples were collected and tested for respiratory pathogens. The prevalence of respiratory symptoms and pathogens was evaluated and compared in the first (December 10, 2018–December 9, 2019) and second (December 10, 2019–November 30, 2020) years of surveillance. Results: Outpatient visits and admissions for respiratory illness significantly decreased from the first to second year, especially among children. SARS‐CoV‐2 was not detected from any participants in Year 2. Among outpatients and inpatients with respiratory symptoms, the prevalence of respiratory syncytial virus and influenza viruses decreased from the first to second year. In contrast, the prevalence of rhinovirus/enterovirus, metapneumovirus and parainfluenza virus increased. Conclusions: The epidemiology of respiratory viruses in rural Zambia changed during the first year of the COVID‐19 pandemic, suggesting that public health interventions may have had an impact on the introduction and circulation of respiratory pathogens in this area.